Características clínicas y epidemiológicas del paciente con pie diabético atendidos en el servicio de hospitalización de medicina del Hospital II-2 Tarapoto durante el periodo mayo a diciembre del 2016 - Huamanchumo Barrientos, Carlo Valentino (2017)
Objective: To determine the clinical and epidemiological characteristics of diabetic foot patients treated at the Tarapoto II-2 Hospital, from May to December 2016. Methodology: The present is a descriptive non-experimental, cross-sectional retrospective study; design based on the review of 53 Clinical Histories of patients who were hospitalized in the medical service of Tarapoto II-2 Hospital between May and December of 2016 and who met the Inclusion and exclusion criteria. Results: from about 53 patients diagnosed with diabetic foot, 64.15% were male. 41.51% are patients who are 60 years of age or older. In 43.40% of the total patients, 15 to more years of evolution of diabetes mellitus were present. According to the time of "Diabetic foot" was found 54.72% with 15 to more days of evolution. According to the part of the affected member; with 39.62%, the toes were the most affected area. Within the signs and symptoms both flossis and ulcers were found to be 100%. Glycemia above 300 mg / dl was found to be 47.17% in 52.83% of patient’s values below 1.4 mg / dl creatinine, in 75.47% of the patient’s values> 10,000 / mm3 of leukocytes. Results ECO DOPPLER: 20.75% severe arterial obstruction was found. Radiography, 11.32% were found signs of osteomyelitis. More frequent late complications: 54.72% of patients had neuropathy; 37.74% presented nephropathy along with neuropathy. More frequent co-morbidities were observed in 41.51% of patients. According to Wagner's classification, the most frequent was grade IV with 33.96%. The most used therapeutic combination with 28.30% was ciprofloxacin + clindamycin. 87% used NPH insulin in combination with crystalline insulin on a mobile scale. 35.85% of the patients underwent surgical cleaning + cures and amputation of the affected limb was achieved. In 30.19% of the patients, surgical cleaning + cures + amputation were performed and all of them belonged to grade IV of the Wagner classification. Conclusions: In this study we found a higher incidence of diabetic foot in the male sex, with a higher percentage in the age group above 60 years of age, presenting a disease time of more than 15 days, was found to be a complication Late to neuropathy and comorbidity to hypertension, with more frequent signs and symptoms such as flogosis and ulcers. As in patients with DOPPLER ECO with severe arterial insufficiency, they are more likely to undergo amputation of the affected limb. It was also concluded that the therapeutic combination of ciprofloxacin with clindamycin and the use of NPH insulin with crystalline insulin on a mobile scale were more frequently used